ESQ Dalam Kepemimpinan Pendidikan - Ridho, Ali (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2016)
Education which is a system in the perspective of anthology is an attempt to humanize humans by an appropriate manner to achieve very high humane values as an attempt to change as well as to move the cultural values to any individual in society. But this view is difficult to achieve when the belief that a person's success will occur due to the efforts started early in order to organize their future without having an education. This paper will provide a breakthrough through leadership of education that is not only based on good intellectual ability, but also good emotional and spiritual. With the result that it will contribute qualified modern human resources. Modern human Resources is a human being who has the potential of ad equated intellectual quality. However, sometimes the potential is empty because it is not matched by the quality of the good faith or emotional. In the fact, they (modern humans) have good reasoning capability. However, the success which is useful in the future whether for themselves, the community, the nation and the state are not only enough by having logical thought only. But, it also requires EQ Emotional Quotient (level of emotional or personality) , CQ Creativity Quotient (level of creativity) and SQ Spiritual Quotient (level religiosities or faith and devotion to God. Thus , the national education system must be able to provide a solution- which is able to break of the empty circle of values and morals happening in education system around us . the empty circle we must combine as well as put the intellectual intelligence , emotional intelligence , and spiritual intelligence known as ESQ in order to get balance between the fulfillment of rights and vertical or horizontal obligations. ESQ is a role of the leadership of its resources which include Human Resources and Natural Resources with the organization as a model of leadership in education. ESQ if applied in educational leadership level, it would be beneficial along with the growth and development of the educational organization with the growth of moral values.